PEMBUATAN APLIKASI PROSES BISNIS, RISET KEBUTUHAN AUDIENS, SERTA PEMBUATAN LAMAN WEBSITE UNTUK PENINGKATAN EFISIENSI PROSES BISNIS - I Gusti Putu Wisnu Wardhana; I Wayan Santiyasa; Ida Ayu Gde Suwiprabayanti Putra (Jurnal Pengabdian Informatika, 2024)
This report documents a community service project focused on the socialization of business process automation applications at PT. The Nomads Group. The main objective of this activity was to enhance the operational effectiveness of the organization and strengthen audience engagement. This project encompassed three main areas: Automation Project, Data Project, and Website Support. Through survey methods, data analysis, and the development of automation solutions, this project successfully improved internal process efficiency and broadened understanding of audience needs.